Language Instruction in Indonesian Elementary Schools Through Computer Assisted Language Learning: A Library Research Review - Muzaki, Ferril Irham; Barus, Yohannes Kurniawan; Tohir, M Anas; Ahdhianto, Erif; Utama, Candra; Putra, Arda Purnama (English Department, Universitas Negeri Surabaya, 2023)
In elementary institutions around the globe, including in Indonesia, computer-assisted language learning (CALL) has gained popularity. Typically, the CALL procedure consists of four stages: preparation, instruction, practice, and evaluation. Preparation includes setting learning goals and choosing software and multimedia. During teaching, teachers present software and multimedia tools and lead pupils. Students improve their language skills individually using software and multimedia materials. Assessing pupils' language skills is the last step. However, successful implementation of CALL in Indonesian elementary schools requires resolving several obstacles, such as the scarcity of trained instructors and the need to adapt CALL to the context of Indonesia. In addition, it is crucial to balance the use of technology with traditional teaching techniques, such as group activities and face-to-face interactions. The results show that (1) language learning results based on AI relates on computer science mastery level, (2) ICT literacy relates on capabilities in operating CALL (3) Artificial Intelligence viewed a tool to teach language learning, and (4) language learning should create learning environment based on community. CALL could be a potent instrument for enhancing language proficiency and preparing Indonesian students for the challenges of the digital era if it receives adequate funding and support.